The Effect of Return On Assets, Return On Equity, Net Profit Margin and Current Ratio on Stock Prices in Oil and Gas Sub-Sector Mining Companies on the Indonesia Stock Exchange for the 2015-2019 Period - Elda Nadia Pasaribu; Junawan; Rahima Br Purba (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This study aims to examine the effect of Return On Assets, Return On Equity, Net Profit Margin and Current Ratio on stock prices in oil and gas sub-sector mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This type of research is quantitative research. The sample used in this study was obtained by saturated sampling method with a total sample of 8 companies. The test method used is multiple linear regression analysis, classical assumption test (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), model feasibility test (F test and analysis of the coefficient of determination (R2)) and hypothesis testing using t test with tools. SPSS (Statistical Product and Service Solutions). The results of this study indicate that testing the hypothesis (t test) the effect of Return On Assets, Return On and Current Ratio partially positive and significant effect on stock prices, while Net Profit Margin has no positive and significant effect on stock prices. F test shows the effect of Return On Assets, Return On Equit, Net Profit Margin and Current Ratio simultaneously have a positive and significant effect on stock prices.